2020
DOI: 10.1016/j.aop.2020.168073
|View full text |Cite
|
Sign up to set email alerts
|

Quantumness and memory of one qubit in a dissipative cavity under classical control

Abstract: Hybrid quantum-classical systems constitute a promising architecture for useful control strategies of quantum systems by means of a classical device. Here we provide a comprehensive study of the dynamics of various manifestations of quantumness with memory effects, identified by non-Markovianity, for a qubit controlled by a classical field and embedded in a leaky cavity. We consider both Leggett-Garg inequality and quantum witness as experimentally-friendly indicators of quantumness, also studying the geometri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 117 publications
(144 reference statements)
0
15
0
Order By: Relevance
“…Quantum decoherence implies a rapid reduction of the off-diagonal terms of the bipartite reduced density matrix. The quantity for measuring the entanglement between the different parts of the composite system is the Concurrence [2,6]. The Concurrence for the evolution of this state can be computed as…”
Section: A Initial Maximally Entangled States |φ±mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum decoherence implies a rapid reduction of the off-diagonal terms of the bipartite reduced density matrix. The quantity for measuring the entanglement between the different parts of the composite system is the Concurrence [2,6]. The Concurrence for the evolution of this state can be computed as…”
Section: A Initial Maximally Entangled States |φ±mentioning
confidence: 99%
“…Many different approaches have studied the entanglement properties of bipartite systems in different frameworks. In [6], authors have studied quantum correlations in a two-qubit system coupled to either a common bath or two different baths, focusing on environmental memory effects induced on the bipartite system. In [7], it has been proposed the used of the Quantum Zeno effect to protect the degradation of the entanglement for two atoms in a lossy resonator.…”
mentioning
confidence: 99%
“…In this way, the control and manipulation of the decoherence can be exploited to enhance the entanglement between the system and its environment. It is proven that the entanglement of the induced steady state between a two-level atom and its spontaneous emission excitation is manipulated by detuning the intensity and relative phase of the fields [ 49 , 50 , 51 , 52 , 53 , 54 ]. It is worth noting that the hybrid entanglement between a photon and an atom has applications in quantum tools, such as quantum networks [ 55 ], quantum repeater [ 56 , 57 ], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the entanglement between two such qubits, which are embedded in two independent cavities, can be preserved for a long time [52]. Moreover, non-Markovianity [53][54][55], quantum Fisher information [56,57], quantum speedup [54], coherence dynamics [58] and quantumness [55] of such a model have been studied.…”
Section: Introductionmentioning
confidence: 99%